Detection of an Abnormal Plasma Clot Structure by a Simple Rigidity Assay - Carr, Marcus E, Jr.; Blatt, Philip M; Roberts, Harold R; Brooker, Jeff Z; Hermans, Jan (Thrombosis and Haemostasis, 1979)
We report here on a patient whose abnormal fibrin clot was detected via the measurement of clot rigidity with a simple buoyant inner cylinder elastometer. The patient’s clinical coagulation studies were all within normal limits except for prolonged thrombin and reptilase clotting times and a high level of fibrin split products. The measured rigidity of the patient’s clot was approximately ten times lower than that of a clot formed from normal pooled plasma. Light scattering studies indicated that this modified structure was not caused by a gross change in gel fiber morphology. Antithrombin activity was eliminated as a possible cause of the altered clot structure; this suggests the possibility of a modified fibrinogen. Abnormalities in the reptilase time and fibrinogen levels in two siblings support the hypothesis that the modification is an inherited defect. We suggest that the simple measurement of rigidity can be used routinely to detect abnormalities in plasma clot structure. The screening for such disorders should be of importance to clinician, patient, and biochemical researcher.